Using built-in functions of Adobe Acrobat Pro DC to help the selection process in systematic review of randomized trials - Nur, Selin; Adams, Clive E.; Brailsford, David F. (BioMed Central, 2016)
This letter describes a simple way of using Adobe Acrobat Pro DC to help select and auto-extract data from Portable Document Format (PDFs) of randomised trials in order to assist swift early selection of trials for a systematic review